Optical properties of amorphous Ge1-x Se (x) and Ge1-x-y Se (x) As (y) thin films - optical gap bowing and phonon modes - Lee, Hosuk; So, Hyeon Seob; Lee, Hosun; Shin, Hae-Young; Yoon, Seokhyun; Ahn, Hyung-Woo; Kim, Su-Dong; Lee, Suyoun; Jeong, Doo-Seok; Cheong, Byung-ki (KOREAN PHYSICAL SOC, 2014)
We investigated the optical properties of Ge1-x Se (x) and Ge1-x-y Se (x) As (y) amorphous films by using spectroscopic ellipsometry and Raman spectroscopy. The dielectric functions and absorption coefficients (alpha) of the amorphous films were determined from the measured ellipsometric angles (I,Delta). We obtained the optical gap energies and the Urbach energies from the absorption coefficients and found a strong bowing effect in the optical gap energy of Ge1-x-y Se (x) As (y) , where the endpoint binaries were Ge0.50Se0.50 and Ge0.31As0.69. Based on the correlation between the optical gap energies and the Urbach energies, we attributed the large bowing parameter to electronic disorder. Using Raman spectroscopy, we measured the phonon modes and discussed the composition dependence of the phonon peak frequencies and lineshapes in terms of structural units. Based on the composition dependence of the phonons in Ge1-x-y Se (x) As (y) , we identified the phonon modes of Ge0.31As0.69. A resonant Raman phenomenon was observed in Ge0.40Se0.60 at a laser excitation of 514 nm (2.41 eV). We verified that this laser energy corresponded to the transition energy of Ge0.40Se0.60 by using the second derivative of the dielectric function of Ge0.40Se0.60.
Keywords: RESONANT RAMAN-SCATTERING; ELECTRONIC-STRUCTURE; CHALCOGENIDE GLASS; CRYSTALLINE; DEPENDENCE; DISORDER; SPECTRA; SILICON; ORDER